Athlete Training Management System (ATMS) - Mustafa, Syasya Farzana; Marjudi, Suziyanti (Applied Information Technology And Computer Science, 2026)
Centralized management is essential in upkeeping the efficiency of athlete management, current reliance on manual methods such as physical log books and spreadsheets at university sports centers leads to redundancy, inefficiency, and errors. This study aims to design, develop, and test a web-based Athlete Training Management System (ATMS) that centralizes training-related activities for athletes, coaches, and team managers. Agile methodology has been used to develop ATMS. The system utilizes object-oriented design principles and incorporates features like digital log books, automated reminders, and training schedules. Findings demonstrate that the ATMS significantly improves communication, reduces redundancy, and organize training management processes. The discussion highlights the potential of a centralized digital platforms to enhance efficiency in sports training and suggests further integration of advanced analytics to support data-driven decision-making in athlete development.